Pengaruh Service Quality Terhadap Customer Satisfaction dan Customer Loyalty (Studi Kasus Pada LP3I Karang Tengah, Tangerang) - syukron sazly (Universitas Bina Sarana Informatika, 2018)
ABSTRACT In the concept of service quality, customer satisfaction and customer loyalty is related to each other. The level of service quality which is the discrepancies between customer expectation and perception will affect customer satisfaction and customer satisfaction ensured to affect customer loyalty as well. And the level of service quality determined by a few variables where customer perceived and expected. The research analyzed the existence of correlation and influence between customer satisfaction and customer loyalty at LP3I Karang Tengah, Tangerang, Banten Province. Connected with the Research Method , This research is descriptive quantitaTive research by asking responden to fill in the quessionaire that given, The respondena are the students of LP3I Karang Tengah who represent their level and their major. We use purposive sampling technic to collect the data from 155 students of this institution in the period of June 1–July 31, 2009 . The data statistically has been analyzed by SPSS 16. with the 95 % significance degree. The variables which form customer satisfaction in this research are Tangible (X1) , Reliability (X2), Responsiveness (X3) , Assurance (X4) and Emphaty( X5) as Independent Variables that adopted from servqual concept. Meanwhile , Relationship, Partnership and Ownership adopted from locking loyalty concept form customer loyalty( Y) as dependent variable. To know the normality of the data we use One-Sample Kolmogorov-Smirnov Test, and the result indicates the data is normal in distribution.. T-Test is used to test the impact of independent variable to dependent variable partially. The Result, only Tangible (X1) dan X3 (Responsiveness) partally affect significantly to Loyalty (Y). F-Test is used to test the impact of independent variable to dependent variable simultanously. The Result,simultanously, Tangible (X1) , Responsiveness (X3) , Assurance (X4) and Emphaty( X5), affect significantly to Loyalty (Y). Meanwhile The Linier Regression Test resulted R suare 0.77, that indicate all variables of Customer Satisfaction affect 77 % significantly to Customer Loyalty (Y). Keywords ; Service Quality, Customer Satisfaction, Customer Loyalty